The use of the self-monitoring technique in writing among polytechnic students / Maxwell March Joseph - Joseph, Maxwell March (2012)
This study aims to investigate the effectiveness of the self-monitoring technique in writing among students. Diploma students (N==100) from the Mechanical Engineering Department, Kuching Polytechnic Sarawak were selected for this study. The experimental design was deployed for this study whereby students were divided into the treatment group (Group 1) and the controlled group (Group 2). Descriptive statistics, t-test and AVONA were used to tabulate the data obtained from the study. A questionnaire survey was also carried out to elicit students' responses toward the self-monitoring technique. The survey revealed that majority of students (78%) had positive attitude towards the self-monitoring technique. The data analysis showed that there was a moderate significant of difference between the scores obtained by Group 1 and Group 2 on the effectiveness of the self-monitoring writing technique.